Petrology and Geochemistry of a Pluton of the Saanich Granodiorite Complex, Helmcken Land District, Vancouver Island, B. C. - Leriche, Peter (My University, 1980)
The thesis pluton is part of the Saanich granodiorite batholithic complex on south-east Vancouver Island. The pluton is 11 Km by 2 Km, elliptical and trends NW-SE.
Petrographically its mineral composition is that of a granodiorite. Alteration is fairly intense as shown by plagioclase and potassium feldspar altering to sericite, as well as biotite and hornblende altering to chlorite. Deformation textures were observed in the form of strained quartz and bent cleavage in biotite.
From chemical analyses it was found that the granodiorite represents part of a fractionation process along a calc-alkaline trend. The magma was derived from partial melting of the lower crust.
Keywords: petrology; geochemistry; pluton; granodiorite